Quantification of golfer-club interaction and club-type's affect on dynamic balance during a golf swing - Shan, G.; Zhang, X.; Li, X.; Hao, W.; Witte, K. (International Journal of Performance Analysis in Sport, 2011)
The current study aimed to provide a holistic picture of efficient golf swing and to determine the club contribution to weight shift patterns. Synchronized data from 3D motion capture (12 cameras, 250 Hz, VICON v8i) and ground reaction force (KISTLER platforms) were collected from 13 advanced golfers. The results showed that a) the club's dynamic influence was closely related to wrist and elbow control, which determined the degree of separation between centre-of-ground-reaction-force and centre-of-gravity of a golfer; b) a Driver has more influence on a golfer's weight transfer than an Iron; c) Club head speed is related to the coordination between shoulder and hip joint; and d) the ball release velocity is influenced by wrists"uncock" (a combination of hand extension and ulnar abduction for accelerating the club to its maximum velocity) at ball contact. Via the novel protocol that customizes to subjects' individual anthropometrical data and separates the body-club system, the current study presents both individual contributing components and more insight view on subjects' golf swing using different clubs.